Assessment of Dental Arch Parameters in Turkish Twins - Birant, Sinem; Koruyucu, Mine; Kasimoglu, Yelda; Veznikli, Mert; Seymen, Figen (MRE PRESS, 2022)
Background: The aim of this study is to investigate the relative contributions of genetic and environmental factors to variations in dental dimensions in a sample of Turkish twins, and to estimate heritability using dental casts. Study design: The study samples were selected from the twin children between 3-15 years old who referred for their first dental examination. Fifty nine monozygotic and one hundred and forty three dizygotic twin pairs were examined in the study. The alginate impression material used to create the plaster model of maxilla and mandible. Anterior arch width, posterior arch width, arch length and arch circumference were measured on models prepared from measurements taken for both maxilla and mandible with digital caliper. The similarities and differences of the measurements were compared between pairs of twins and zygocytes. Morever, the effects of bad oral habits, bruxism, a result of psychosocial factors on measurements were examined. Statistical analysis was performed using Paired T Test, Wilcoxon Test and Mann Whitney U test. Results: A total of 404 dental models of 118 (29.2%) monozygotic and 286 (70.8%) dizygotic twins were evaluated. There was no statistical difference between sibling pairs in both monozygotic and dizygotic twins. The measurement similarity between twin siblings differed according to zygosity in all measurements (p<0.05). It has been observed that the finger sucking and mouth breathing affect the dental arch measurements (p<0.05). Conclusion: These results indicate that the differences in dental arch dimensions between monozygotic twin pairs are less than the difference between dizygotic twin pairs.
Keywords: Twin; Arch dimension; Genetic factors; GENETIC CONTRIBUTION; OCCLUSAL VARIATION; TOOTH; SIZE; FORM; DIMENSIONS; MORPHOLOGY; WIDTHS; Dentistry, Oral Surgery & Medicine; Pediatrics